A glycoproteomics study of Staphylococcus epidermidis biofilm / Farah Abd. Hadi - Abd. Hadi, Farah (2019)
Staphylococcus epidermidis is the leading opportunistic bacteria among the coagulasenegative staphylococci (CoNS) which caused many biofilm-associated infections. Biofilm exhibits an extraordinary resistance towards antimicrobial agents. To date, biofilm-associated infections have increased worldwide with no promising treatment. Yet, the impact of protein glycosylation on biofilm and antibiotic resistance is still not understood.